Feasibility Study Analysis Of The Development Of Ansi Decoration Smes In Bintunan Village, Batiknau District, North Bengkulu - Agrianti, Lara; Susena, Karona Cahya; Gayatri, Ida Ayu Made Er Meytha (Utami Publisher, 2025)
This study aims to analyze the financial feasibility of developing UMKM Ansi Decoration located in Bintunan Village, Batiknau District, North Bengkulu Regency. The analysis was conducted using financial feasibility methods, including the Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), and Gross Benefit Cost Ratio (Gross B/C). The results show that at a discount rate of 10%, the business is feasible to operate. The Payback Period (PP) was 7 months and 5 days in 2023 and 6 months and 8 days in 2024, with an NPV of Rp206,300,619.83 (>0), an IRR of 55.33% (>10%), and Gross B/C ratios of 1.672 and 1.915 (>1). Thus, the development of UMKM Ansi Decoration is declared feasible to be implemented and further expanded.